Timbali Technology Incubator : South Africa Case Study - World Bank (Washington, DC, 2014)
Timbali technology incubator in the Mpumalanga region of South Africa seeks to help rural farmers whose livelihood has been undercut by high-volume large farms. Supported by government financing and fee-based services, Timbali is largely based on a franchise model. Its clients supply cut flowers to Amablom, Timbali's commercial arm. Individual clients can begin generating revenue almost immediately. Timbali helps clients both onsite and off, training them in business methods and helping find loans to get started. It is helping clients expand into other product lines and value-added food processing, and plans to export its model into other parts of South Africa. In this context, this report presents summary, background and context, strategic vision, mission, and targets, Timbali's distinctive features, brand and market position, approach to incubation, institutional set-up, business model, staffing, outcomes and conclusions, critical success factors, lessons learned and implications for agribusiness incubators, and future goals.